"Give and take": how notions of sharing and context determine free peer-to-peer accommodation decisions. Issue 1 (2nd January 2018) - Geiger, Alina; Horbel, Chris; Germelmann, Claas Christian
ABSTRACT: Building on social exchange theory and value co-creation, the present paper investigates how obligations and expectations of reciprocity as well as value-in-social-context shape preferences for or against free accommodation sharing. Applying a grounded theory approach, we propose a novel theoretical framework linking the notions of mutual giving and taking as asset or burden to the contextual characteristics of travelers' accommodation decisions. Our findings contribute to a better understanding of consumers' perceptions of and decisions in favor of true sharing accommodation options. Based on our framework, we derive propositions to stimulate further research and provide implications for actors in the paid accommodation market.